Tropical medicine for the 21st century. - De Cock, K. M. (BMJ Group, 1995)
The specialty of tropical medicine originated from the needs of the colonial era and is removed from many of the health care requirements of tropical countries today. Tropical medicine concentrates on parasitic diseases of warm climates, although other infections and diseases related to poverty rather than climate dominate medicine in developing countries challenged by population pressure, civil strife, and migration. In the new century, tropical medicine would best be absorbed into the specialty of infectious diseases, which should incorporate parasitic diseases, travel medicine, and sexually transmitted diseases. Pressing questions for health care and research in developing countries concern the provision of appropriate services for problems such as HIV/AIDS, tuberculosis, sexually transmitted diseases, and injuries. The question of how to provide appropriate clinical care in resource poor settings for the major causes of morbidity and premature mortality has been neglected by donors, academic institutions, and traditional tropical medicine.